Evaluation of transportation network in AL- Fallujah city - Mhana, Khalid Hardan (Anbar Journal of Engineering Sciences, 2021)
The city of Fallujah suffers from bad design in their network and it still dominated by the same pattern of the road and street network system that was produced by the previous stages of the development of the city, which is awaiting the necessary and appropriate solutions, which calls for planning to modernize the road network and streets in it that can accommodate the reality of the city’s condition and the proposed expansions for its subsequent urban growth. The transportation network in Fallujah city was chosen as a case study, the network was divided into roads and intersections, the evaluation included two main roads and eleven sectoral roads, eleven arterial roads, and twenty-five intersections. The network was evaluated in three stages, the first stage was traffic flow and service level, the second stage was evaluating the network in terms of road and intersections marking, while the third stage concerned with evaluating the network in terms of sustainability. The HCS 2010 program was applied to evaluate the first stage, while the second and third stages were evaluated based on the field survey. The results of the first stage showed that most parts of the network in the northern zone suffer from traffic problems and have a low level of service, while most parts of the network in the southern zone have a high service level and enjoy high traffic flow. Most parts of the network were suffered from bad marking, which causes many problems for the users of this network. Related to sustainability, we note a lack of interest on the part of designers or decision-makers. It was concluded that traffic solutions should be economically feasible for some parts of the network, which would lead to improving the network’s performance at the level of the three stages.